Dynamic Catalytic Highly Enantioselective 1, 3‐Dipolar Cycloadditions. (3rd August 2021) - Yildirim, Okan; Grigalunas, Michael; Brieger, Lukas; Strohmann, Carsten; Antonchick, Andrey P.; Waldmann, Herbert
Abstract: In dynamic covalent chemistry, reactions follow a thermodynamically controlled pathway through equilibria. Reversible covalent‐bond formation and breaking in a dynamic process enables the interconversion of products formed under kinetic control to thermodynamically more stable isomers. Notably, enantioselective catalysis of dynamic transformations has not been reported and applied in complex molecule synthesis. We describe the discovery of dynamic covalent enantioselective metal‐complex‐catalyzed 1, 3‐dipolar cycloaddition reactions. We have developed a stereodivergent tandem synthesis of structurally and stereochemically complex molecules that generates eight stereocenters with high diastereo‐ and enantioselectivity through asymmetric reversible bond formation in a dynamic process in two consecutive Ag‐catalyzed 1, 3‐dipolar cycloadditions of azomethine ylides with electron‐poor olefins. Time‐dependent reversible dynamic covalent‐bond formation gives enantiodivergent and diastereodivergent access to structurally complex double cycloadducts with high selectivity from a common set of reagents. Abstract : A highly enantioselectively catalyzed dynamic covalent one‐pot‐tandem 1, 3‐dipolar cycloaddition of azomethine ylides to α′‐alkylidene‐2‐cyclopentenones is described. Time‐dependent enantio‐ and diastereodivergent synthesis was achieved by using the same set of reagents. A reversible cycloaddition of the kinetically favored product enables the interconversion to its more stable thermodynamically favored product through a chiral complex‐mediated process.